Corrosion prevention of steel sample in aqueous solutions and its mechanical properties - Yeap, Leong Hooi (2010)
Corrosion has become a main issue for all engineering sector in these few decades. The main purpose of this project is to investigate the corrosion prevention method in order to slow down the process of corrosion and to investigate the effect of the prevention method on the mechanical properties of those sample specimens. Three methods applied on the steel samples which are nickel electroplating, zinc electroplating and powder coating. The corrosion rate was determined by using weight loss method in immersion test according to ASTM G31, whereas the mechanical properties to be investigated were hardness and tensile test. The dimension of tensile test specimens was followed the ASTM E-8M. The results obtained show that the corrosion rate of the coated specimen was lower than that of the specimen without coating. The specimen with nickel electroplating has the lowest corrosion rate among the coated specimens, followed by powder coating and zinc electroplating. The coated specimens also have the higher value in hardness; yield strength and ultimate tensile strength, where the nickel electroplating has the highest value among all others specimens.